2019
DOI: 10.1017/jfm.2019.595
|View full text |Cite
|
Sign up to set email alerts
|

Thermal fluctuations in capillary thinning of thin liquid films

Abstract: Thermal fluctuations have been shown to influence the thinning dynamics of planar thin liquid films, bringing predicted rupture times closer to experiments. Most liquid films in nature and industry are, however, non-planar. Thinning of such films not just results from the interplay between stabilizing surface tension forces and destabilizing van der Waals forces, but also from drainage due to curvature differences. This work explores the influence of thermal fluctuations on the dynamics of thin non-planar film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…A long-wave approximation for thin films, and also for jets, has been used to derive stochastic lubrication equations (SLE) from FH: the jet SLE by Moseler & Landman (2000), and the planar-film SLE by Grün, Mecke & Rauscher (2006), Davidovitch, Moro & Stone (2005) and Durán-Olivencia et al (2019). Notably, numerical solutions to the jet SLE (Moseler & Landman 2000;Eggers 2002;Zhao, Lockerby & Sprittles 2020) and the planar-film SLE (Grün et al 2006;Nesic et al 2015;Diez, González & Fernández 2016;Durán-Olivencia et al 2019;Shah et al 2019) demonstrated that noise can accelerate the rupture process, in agreement with experimental analyses (Becker et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A long-wave approximation for thin films, and also for jets, has been used to derive stochastic lubrication equations (SLE) from FH: the jet SLE by Moseler & Landman (2000), and the planar-film SLE by Grün, Mecke & Rauscher (2006), Davidovitch, Moro & Stone (2005) and Durán-Olivencia et al (2019). Notably, numerical solutions to the jet SLE (Moseler & Landman 2000;Eggers 2002;Zhao, Lockerby & Sprittles 2020) and the planar-film SLE (Grün et al 2006;Nesic et al 2015;Diez, González & Fernández 2016;Durán-Olivencia et al 2019;Shah et al 2019) demonstrated that noise can accelerate the rupture process, in agreement with experimental analyses (Becker et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…while the lower bound is dictated by the region where curvature goes from practically zero in the flat part to 2/R c in the curved part. This leads to R pb √ h o R c , as discussed in more detail in Shah et al [35]. We now perform a scaling analysis to demonstrate that the problem is governed by two dimensionless parameters.…”
Section: Problem Formulationmentioning
confidence: 72%
“…The mobility term (rh 3 ) is discretized as per the positivity-preserving scheme discussed in Diez et al [34]. Based on our previous work [35], we use r = 0.05 and t = r 2.25 , and confirm that the presented simulation results for lifetimes are grid and time-step size independent.…”
Section: Numerical Implementationmentioning
confidence: 84%
See 2 more Smart Citations